Effect of Chicken Fertilizer Combination and Concentration Of Organic Liquid Fertilizer (LOF) on Growth and Results of Sawi Plant (Brassica Junceae L.) Shinta Variety - R, Budiasih; Hadian, Sandi; Salim, Mohamad Agus; Subandi, M (Asian Journal of Agriculture and Rural Development, 2019)
This research was aimed to test the efficacy of organic liquid fertilizer and to know its effect on the growth and yield of sawi plant. The environmental design used was Randomized Block Design (RBD), consisting of nine treatments and each repeated three times. The combination treatment of chicken manure and liquid organic fertilizer were tested, namely : A = Stable chicken manure 0 ton ha-1 + LOF 0 ml L-1 Solution, B = Stable chicken manure 0 ton ha-1 + LOF 3 ml L-1 Solution, C = Stable chicken manure 0 ton ha-1 + LOF 6 ml L-1 Solution, D = Stable chicken manure 10 ton ha-1 + LOF 0 ml L-1 Solution, E = Stable chicken manure 10 ton ha-1 + LOF 3 ml L-1 Solution, F = Stable chicken manure 10 ton ha-1 + LOF 6 ml L-1 Solution, G = Stable chicken manure 20 ton ha-1 + LOF 0 ml L-1 Solution, H = Stable chicken manure (dung) 20 ton ha-1 + LOF 3 ml L-1 Solution, I = Stable chicken manure 20 ton ha-1 + LOF 6 ml L-1 Solution. The results showed that the combination of chicken manure and liquid organic fertilizer had a significantly different effect on all growth parameters and yield of Shinta variety mustard plants, using a combination of chicken manure dosage of 20 tons ha-1 and liquid organic fertilizer with a concentration of 6 ml L- 1 Solution give a better influence on the growth and yield of Shinta variety mustard plants.